2018
DOI: 10.1039/c8ta04005b
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous membranes with surface migration of functional groups for ultrafast wastewater remediation

Abstract: Nanofibrous membranes with surface migration of hydrophilic and negatively charged groups were designed for ultrafast water purification and smart dye separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…Carbon is regarded as an excellent adsorbent for the removal of several pollutants in aqueous solutions. 6 Furthermore, some new carbon materials have been developed including carbon nanotubes (CNTs) 7 and carbon nanobers (CNFs) 8 which show a high degree of adsorption during purication process of water. However, the efficacy of these materials is limited to only certain types of pollutants e.g., organic compounds and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon is regarded as an excellent adsorbent for the removal of several pollutants in aqueous solutions. 6 Furthermore, some new carbon materials have been developed including carbon nanotubes (CNTs) 7 and carbon nanobers (CNFs) 8 which show a high degree of adsorption during purication process of water. However, the efficacy of these materials is limited to only certain types of pollutants e.g., organic compounds and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized PEI/PVDF nanofibers was used for the removal of MO dye, which exhibited good adsorption capacity (633 mg/g) and can be reused more than 10 times. Xu et al fabricated PES nanofibers and enhanced its adsorption capacity by blending with amphiphilic copolymer like methyl methacrylate and sodium styrene sulfonate (P(MMA-SSNa) [128]. They found that negatively charged sulfonated groups migrated onto the surface of nanofibers and enhanced their adsorption rate and adsorption capacity towards the removal of MB as shown in Figure 5.…”
Section: Epnfs Blends As Adsorbent For Dyes Removalmentioning
confidence: 99%
“…The enhancement of pore volume and preparation of ultrathin membranes are two common solutions. The nanobers-based ltration membranes, e.g., porous electrospun nanobers, [21][22][23][24] have large pore volumes and abundant channels for high water permeability. Even though the electrospun nanober membranes have achieved great progresses in water treatment elds, some problems still hinder their applications, 25 such as specic preparation equipment, high voltage, and organic solvents.…”
Section: Introductionmentioning
confidence: 99%